4-Methoxycinnamic acid – An unusual phenylpropanoid involved in phenylphenalenone biosynthesis in Anigozanthos preissii. (September 2015) - Hidalgo, William; Kai, Marco; Schneider, Bernd
Graphical abstract: An unusual phenylpropanoid, 4-methoxycinnamic acid, was used in 13 C-labeled form as a substrate to demonstrate its incorporation as an intact unit during the biosynthesis of 4′-methoxyanigorufone, which is reported here for the first time as a natural product. Highlights: 4-Methoxycinnamic acid (2 ) was detected as natural phenylpropanoid in A. preissii . 4′-Methoxyanigorufone (4 ) was reported for first time as a natural product. Compound2 was biosynthetically incorporated as an intact unit into compound4 . Abstract: In vitro root cultures of Anigozanthos preissii and Wachendorfia thyrsiflora (Haemodoraceae) are suitable biological systems for studying the biosynthesis of phenylphenalenones. Here we report how we used these root cultures to investigate precursor–product relationships between phenylpropanoids and phenylphenalenones whose phenyl rings share identical substitution patterns. Four phenylpropanoic acids, including ferulic acid and the unusual 4-methoxycinnamic acid, were used in 13 C-labeled form as substrates to study their incorporation into phenylphenalenones. In addition to the previously reported 2-hydroxy-9-(4′-hydroxy-3′-methoxyphenyl)-1 H -phenalen-1-one (trivial name musanolone F), 2-hydroxy-9-(4′-methoxyphenyl)-1 H -phenalen-1-one (proposed trivial name 4′-methoxyanigorufone) was found as a biosynthetic product in A. preissii . The carbon skeleton of 4′-methoxycinnamic acid was biosynthetically incorporated as an intact unit including its 4′- O -methyl substituent at the lateral phenyl ring. 4′-Methoxyanigorufone is reported here for the first time as a natural product.